An evaluation study of enzyme-linked immunosorbent assay (ELISA) using recombinant GRA1 protein for detection of igg antibodies againts Toxoplasma gondii infections - Nina Difla Muflikhah; Wayan Tunas Artama (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2019)
Reliable laboratory testing is important to detect Toxoplasma gondii infection and focuses on improving the low cost and easy to use the diagnostic instrument. Enzyme-linked immunosorbent assay (ELISA) method can be used to determine a large number of samples within a short period of time which based on antibody or antigen detection. We tested the sensitivity and specificity of GRA1 protein of as antigen using the ELISA method to toxoplasmosis diagnosis and compared it with commercial ELISA kit. Seventy sera samples were collected and tested using indirect ELISA, commercial ELISA kit and GRA1 protein-coated as antigen. The results showed 48 and 51 samples had positive IgG antibody using ELISA-GRA1 and commercial ELISA kit, respectively. The GRA1 sensitivity and specificity on ELISA were 100% and 86.36%, respectively. Whereas positive predictive value (PPV) was 94.11%. This result indicated that the recombinant GRA1 protein is a highly immunogenic protein in human toxoplasmosis and marker for toxoplasmosis screening.